Artfully yours - Lowell, Joanna (Berkley Romance, 2023)
"Sparks fly between a lordly art critic and a lady forger in this enthralling Victorian historical romance. Nina Finch isn't suited for a life of crime. Raised by her art-forger brother, she can paint like Boticelli. But she'd so much rather be baking gooseberry tarts. She finally has the money she needs to open her own bakery. Unfortunately, her brother's carelessness lands her--and their forgeries--directly under the nose of London's most discerning art critic, Alan De'Ath. De'Ath knows the paintings are fake. He doesn't know that Nina had a hand in their creation. In fact, he offers her a job in his household. Accepting it is the most dangerous thing she has ever done ... Alan takes pride in seeing things other people miss. He plans to catch the forger and cement his reputation. There's only one problem: the closer he gets to the beguiling woman he hired, the less he trusts his perspective. Nina isn't what she seems. But despite their false start, she just might hold the real key to his heart. As Nina and Alan's attraction grows, divided loyalties threaten to pull them apart and shatter their worlds. They'll lose everything, or discover how powerful true love can be ..."--